Prognostic Value of Albumin Levels before Therapy on Survival of Nasopharyngeal Carcinoma Patients - Dita Ria Selvyana; Susanna Hilda Hutajulu; Johan Kurnianda; Fitria Nurul Hidayah (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2022)
Nasopharyngeal cancer (NPC) is a type of cancer in Southeast Asia, with 30-80 cases annually per 10,000 population. Based on the data, about 80% of patients with advanced-stage are diagnosed first, while 20% develop metastases after therapy. A prognostic assessment is essential for the optimization of treatment. Malnutrition is one of the consequences of decreased response to treatment, quality of life, and survival. The patient's albumin determines nutrition. This study was a retrospective study to evaluate the ability of pre-therapy albumin levels to predict long-term mortality in 227 NPC patients at Dr. Sardjito Hospital. Univariate analysis identified albumin as a statistically significant predictive factor for survival (P 0.021). Albumin (ALB) 3.50 was significantly associated with shorter survival. Median Overall Survival showed (OS) ± SE ALB 3.50 vs. ALB 3.50: 9.40 ± 2.56 vs. 17.63 ± 1.51 months, P 0.021, Hazard Ratio (HR) 1.368; 95% CI (1.049–1.783). However, multivariate analysis showed low serum albumin levels before therapy on survival in NPC patients (P 0.778, HR 1.050, 95% CI (0.75–1.469). Treatment was identified as the only independent predictive factor for survival. Albumin before therapy was a potential predictive biomarker to evaluate survival in NPC patients but not an independent predictor.